USE OF MOLECULAR MARKERS IN WHEAT BREEDING FOR RESISTANCE TO LEAF RUST AT THE LUKYANENKO RESEARCH INSTITUTE OF AGRICULTURE - E. R. Davoyan; L. A. Bespalova; R. O. Davoyan; Yu. S. Zubanova; D. S. Mikov; V. A. Filobok; J. N. Khudokormova (Вавиловский журнал генетики и селекции)
Wheat accessions were genotyped with molecular markers linked to wheat leaf rust resistance genes Lr9, r10, Lr19,Lr24, Lr26, Lr34, and Lr37. They included 1920 wheat plants and 46 commercial varieties bred at the Lukyanenko Institute. Basically, the analyzed varieties had the inefficient gene Lr10, poorly effi cient Lr26 and Lr34, or their combinations. The highly effi cient genes Lr9 and Lr24 were not detected. The Lr19 gene, effective in the Krasnodar region, was identified in varieties Pallada and Yara. The resistance gene Lr37 was found in variety Morozko. Within a short time, F2 and F3 plants with introgression of genes Lr9, Lr19, Lr24, Lr37 were obtained. Accessions with combinations Lr24 + Lr37, Lr24 + Lr19, Lr24 + Lr9, Lr19 + Lr37, Lr37 + Lr9, Lr19 + Lr9 were identified. Seven plants with the combination of three genes Lr37 + Lr19 + Lr9 and one with Lr37 + Lr24 + Lr9 were selected.